Factors of Adaptation to New Technologies among Workers of Retirement Age in Lithuania - Šilingienė, Violeta; Poetter, Erika (Information & Media, 2026)
This article presents the results of a study on the adaptation of retirement-age employees to new technologies. The integration of new technologies into work processes necessitates the continuous updating of skills, while older workers often face limited technological literacy, stereotypes, and a lack of learning resources. On the other hand, their professional experience, loyalty, and knowledge transfer skills are important to organizations. The aim of this article is to reveal the factors that determine the adaptation of older workers to new technologies. To achieve this goal, a qualitative study was conducted, and the research data were obtained through semi-structured interviews with 17 older workers employed in Lithuania. The study identified that retirement-age employees face challenges in adapting to new technologies due to rapid technological changes, the need to respond quickly, and the need to constantly update their skills. The study also revealed the factors that determine the adaptation of retirement-age employees to new technologies. Adaptation was found to be a multifaceted process, strongly influenced by individual, organizational, motivational, social, and technological factors. The study was conducted with the objective to pursue insights for further theoretical development, deepening the empirical evidence-based understanding of the factors that would promote the successful adaptation of older workers to new technologies.